1982
DOI: 10.1017/s025292110009744x
|View full text |Cite
|
Sign up to set email alerts
|

Spectra of individual symbiotic stars

Abstract: In connection with the discussion of the individual symbiotic stars, we present low resolution, flux calibrated spectra and high resolution H α profiles for each of 12 objects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
3
3
0
Order By: Relevance
“…The sharp component has a FWHM of about 0.8 Á. The whole Ha profile resembles the profiles of several symbiotic stars observed at high resolution by Oliversen and Anderson (1982). The wings of the line are fairly symmetric about the mean position, with a shift of at most -20 km s -1 relative to the mean of the entire line.…”
Section: Discussionsupporting
confidence: 61%
“…The sharp component has a FWHM of about 0.8 Á. The whole Ha profile resembles the profiles of several symbiotic stars observed at high resolution by Oliversen and Anderson (1982). The wings of the line are fairly symmetric about the mean position, with a shift of at most -20 km s -1 relative to the mean of the entire line.…”
Section: Discussionsupporting
confidence: 61%
“…1 The spectrum of V1329 Cyg has been studied by numerous authors and summarized by Kenyon (1986). Two blueshifted components of [Fe vu] at -200 and -350 km s -1 have been reported, and the Ha line shown by Oliversen and Anderson (1982) is rather similar to our profile of 1984 August 28 except that they also found a strong absorption feature.…”
Section: Introductionsupporting
confidence: 69%
“…Five Ha profiles arranged according to the phases of Nussbaumer et al (1986) are shown in Figure 2. The phase coverage has such large gaps that a smooth change of profile with phase cannot be elucidated, but we can add the profile of May 1979 (cf) = 0.099, Oliversen and Anderson 1982) and four profiles (1983 October 28, cf) = 0.782;1984 May 8, cf> = 0.982;1985 July 24, cf) = 0.441; 1985 October 9, cf) = 0.520; Tamura 1988). It appears that their changes are correlated with the flux-phase relation of Nussbaumer et al (1986).…”
Section: The Ha Profilementioning
confidence: 99%
“…We obtained emission-line profiles of Ha, Hy, [O III] XA4959,5007, He i X5016, He i X4921, Fe il X5018, and Fe il X4924 over almost one cycle of the period, namely 950 days, which is adopted because of the indicated binary nature (Grygar et al 1979). Our observations show time variations of emission-line profiles like those of other typical symbiotic stars (Oliversen and Anderson 1982;Oliversen, Anderson, and Nordsieck 1982;Welty 1983) as well as characteristic differences of profiles among various ions. Therefore, we need reanalyses, in particular, of the measurement of radial velocities determined in previous work (Iijima, Mammano, and Margoni 1981).…”
Section: Introductionsupporting
confidence: 54%
“…Although several authors (Oliversen et al 1982;Oliversen and Anderson 1982;Welty 1983) have recognized the time variation of Ha profiles in other symbiotic stars as well as UV lines of HBV 475 itself (Nussbaumer et al 1986), this is the first detection of the drastic change of the Ha line during the period. Moreover, it can be confirmed that Ha profiles generally correlate to assumed phase.…”
Section: Discussionmentioning
confidence: 87%